Perancangan Ontologi Semantik: Representasi Digital Tokoh Wayang Bali - Wira Putra, I Gede Ngurah Arya; Octavia, Hana Christine; Wiradhanta, Ngakan Made Alit; Pramartha, Cokorda Rai Adi (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 3 (2025): JELIKU Volume 13 No 3, February 2025, 2025)
Balinese wayang faces challenges in data management, such as difficult data integration, information inconsistency, and trouble retrieving relevant data. This article proposes the use of ontology as a solution to improve interoperability and data management efficiency. Ontology enables more effective data integration from various sources, resulting in consistent and accessible information. Additionally, ontology provides benefits such as enhanced data accessibility, reduced redundancy, and improved information accuracy. The implementation of ontology in the Balinese wayang industry is explained through case studies, aiming to enhance the end-user experience, including puppeteers, cultural historians, and researchers, by providing better and more accurate data access.